Nasal Allergen Deposition Leads to Conjunctival Mast Cell Degranulation in Allergic Rhinoconjunctivitis. Issue 4 (July 2014) - Callebaut, Ina; De Vries, Annick; Steelant, Brecht; Hox, Valerie; Bobic, Sonja; Van Gerven, Laura; Ceuppens, Jan L.; Hellings, Peter W.
Background: The naso-ocular interaction in allergic rhinoconjunctivitis is well recognized from epidemiological, clinical, and experimental observations. The precise mechanisms remain incompletely understood. A new mouse model of allergic rhinoconjunctivitis was used to investigate the contribution of mast cells and trigeminal ganglia activation to conjunctival (conj.) inflammation after nasal allergen provocation. Methods: Sensitized mice were exposed to ovalbumin (OVA) via the nose and/or conjunctiva, and conj. homogenates were analyzed for histamine and substance P (using ELISA) and by eosinophil peroxidase (EPO) and beta-hexosaminidase assays. The conj. effects of nasal allergen deposition were compared with those induced by the mast cell activator C48/80 and with pretreatment of the mast cell stabilizer ketotifen or the transient receptor potential channel receptor (TRP) agonist capsaicin. Protachykinin 1 (TAC1) expression was quantified in the trigeminal ganglia using real time polymerase chain reaction. Results: At 1 hour after nasal application of OVA, increased conj. levels of beta-hexosaminidase (0.68 ± 0.03 nm versus 0.56 ± 0.02 nm; p = 0.02), histamine (751.1 ± 52.17 ng/mL versus 546.3 ± 76.91 ng/mL; p = 0.05), and EPO (0.66 ± 0.09 nm versus 0.37 ± 0.03 nm; p = 0.02) were detected compared with saline. Higher levels of TAC1 expression were found in the trigeminal ganglia at 24 hours after OVA application (1326 ± 255 versus 687.5 ± 90.77 TAC1/beta-actin; p = 0.04). Nasal challenge with C48/80 increased substance P and beta-hexosaminidase levels in the conjunctiva, as well as TAC1 expression. Pretreatment with ketotifen resulted in lower levels of substance P as well as TAC1 expression. Destruction of sensory nerves in the nose by capsaicin reduced the OVA-induced conj. levels of substance P, histamine, a beta-hexosaminidase. Conclusion: Nasal allergen deposition in sensitized mice induced trigeminal TAC1 expression and conj. mast cell degranulation. These data represent a significant step forward in understanding the close interaction between nasal and conj. inflammation in allergy.